Hip rotation asymmetries in front crawl and backstroke - Fernandes, A.; Fernandes, A.; Borgonovo-Santos, M.; Carvalho, D. D.; Ferreira, F.; Mezêncio, B.; Vilas-Boas, J. P.; Fernandes, R. J. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Body rotation is typical of the alternated techniques due to the upper limbs actions, usually expressed as the shoulders/hip rotation amplitude. Rotation involves rolling to the right and left sides. Asymmetries were not explored in the backstroke, neither compared between alternated techniques. The current study compared front crawl and backstroke hip rotation to the right and left sides at distinct pace conditions. Six national swimmers (four males, 17±0.8 vs 14 years, 176.8±7.1 vs 164.5±4.9 cm, 73.1±12.9 vs 60.2±2.9 kg) performed four front crawl and backstroke trials at 90% and maximum velocity. A bi-axial Fluid Flow Sensor with a 9 degrees of freedom inertial unit was attached to the swimmers waist, allowing to obtain Euler angles. All upper limbs cycles were analysed, removing the first and the last ones. Paired t-test was used to compare rolling sides and swimming techniques (p.0.05). Hip roll amplitude decreased from 90% to maximum velocity in front crawl (95.6±21.3 vs 79.3±22.2°, p<0.05) but remained in backstroke (104.1±16.6 vs 99.6±27.4°). Hip rotation amplitude was similar between techniques at 90% (95.6±21.3 vs 104.1±16.6°) but not at maximal velocity (79.4±22.2 vs 99.6±27.4°), presenting differences in rolling to the right side (40.6±10.3 vs 54.1±9.9°, p<0.05, respectively). None of the alternated techniques showed asymmetries at any swimming condition, although a tendency to the right side can be observed. Hip roll asymmetries were higher than those already presented in front crawl, evidencing a right side dominance in both swimming techniques (despite no differences proved). Swimmers did not reduce rolling in backstroke when velocity increased, maybe due to the more complex underwater upper limbs motion. Alternated techniques roll with the different magnitude, but asymmetrical characteristics were not exhibited.